How Can Financial Supervisors Improve the Effectiveness of Corporate Governance? - Palmer, John; Hoong, Chang Su (World Bank, Washington, DC, 2012)
New initiatives are under way to improve governance, including guidelines from supervisory standard-setting bodies such as the Basel Committee on banking supervision. These initiatives should help, but more is needed to change board culture and behavior. Financial supervisors have an important stake in ensuring sound corporate governance as a strong underpinning for effective supervision. This paper suggests measures that financial supervisors can take to improve governance in regulated financial institutions. Although governance performance is inherently difficult to assess, supervisors who make extensive use of onsite inspections and actively engage boards and board committees will have a greater chance of improving the quality of governance performance in the financial institutions for which they are responsible.